Recent Research on Balance Disorders - Balkan, Esor (IntechOpen, 2023)
This book provides a comprehensive overview of balance disorders. It discusses the initial approach to patients with balance disorders and presents important studies in the field. It is designed for general practitioners and specialist physicians.